2021
DOI: 10.1542/peds.2020-025056
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Supplemental Nutrition Assistance Program Benefits and Families’ Home Food Environments

Abstract: BACKGROUND AND OBJECTIVES Supplemental Nutrition Assistance Program (SNAP) benefits are designed to buffer families from food insecurity, but studies suggest that most benefits are used by midmonth. In this study, we examined whether the home food environment varies across the SNAP benefits cycle among participating families . METHODS Participants in this mixed-methods study were 30 SNAP participants who were primary caregive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Many families struggled with getting their children to eat enough food or healthier meals. Families with a low-income often do not have the time or resources to cook specific meals for children, to experiment with different types of food, try foods multiple times, and have the added worry that if a child does not like a meal, it could be a waste of resources [54][55][56]. Participants in this study demonstrated additional obstacles for feeding children that are unique to food insecurity, along with the struggle of picky eaters [48,51,53,[57][58][59][60].…”
Section: Struggles To Secure Foodmentioning
confidence: 91%
See 1 more Smart Citation
“…Many families struggled with getting their children to eat enough food or healthier meals. Families with a low-income often do not have the time or resources to cook specific meals for children, to experiment with different types of food, try foods multiple times, and have the added worry that if a child does not like a meal, it could be a waste of resources [54][55][56]. Participants in this study demonstrated additional obstacles for feeding children that are unique to food insecurity, along with the struggle of picky eaters [48,51,53,[57][58][59][60].…”
Section: Struggles To Secure Foodmentioning
confidence: 91%
“…Affordability was mentioned frequently as a struggle to eat, despite most participants reported usage of formal support systems such as SNAP and WIC and informal support systems such as friends and family. This finding was not surprising as food insecurity is often driven by a lack of financial resources [4][5][6][54][55][56]. Particular to the rural context, participant's reliance on their network for food or financial support was notable.…”
Section: Struggles To Secure Foodmentioning
confidence: 97%